2020
DOI: 10.1186/s12887-020-02240-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D toxicity in a pediatric toxicological referral center; a cross-sectional study from Iran

Abstract: Background Vitamin D is an essential element for body health with its supplements generally administered to prevent vitamin D deficiency. Since these supplements are available in domestic settings, vitamin D toxicity may happen in children. Methods All children younger than 12 years who presented to the pediatric emergency department of Loghman Hakim Hospital, Tehran, Iran with history of ingestion of more than 1500 IU/day of vitamin D supplements were enrolled. Patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
3
0
1
Order By: Relevance
“…Lin et al show that younger age is associated with an increased risk of the development of nephrocalcinosis [30]. While Çağlar and Çağlar found no significant difference in age, all patients in their cohort were less than 4 years old [31], a trend which seems consistent with other published reports in children [8,33,34].…”
Section: Vitamin D In Children With Ckdsupporting
confidence: 83%
“…Lin et al show that younger age is associated with an increased risk of the development of nephrocalcinosis [30]. While Çağlar and Çağlar found no significant difference in age, all patients in their cohort were less than 4 years old [31], a trend which seems consistent with other published reports in children [8,33,34].…”
Section: Vitamin D In Children With Ckdsupporting
confidence: 83%
“…Only one child had hypercalcemia, and eight had vitamin D levels more than 100 ng/mL. This study concluded that acute vitamin D toxicity might be a benign condition in Iranian children due to the high prevalence of vitamin D deficiency [13].…”
Section: Discussion and Review Of Literaturementioning
confidence: 69%
“…VDT can be caused by a high dose of vitamin D combined with calcium which will promote hypercalcemia [ 81 ]. The symptoms of hypercalcemia are neurological (confusion, irritability, restlessness, and apathy, and in severe cases, can cause psychosis, stupor, and coma); cardiovascular (hypertension, shortened QT interval which indicates arrythmia, elevated ST segment, bradyarrhythmia, and first-degree heart block), gastrointestinal (abdominal pain, nausea, ulcer, vomiting, polydipsia, anorexia, constipation, and pancreatitis), and kidney symptoms (hypercalciuria, acute kidney injury (AKI), polyuria, polydipsia, dehydration, and nephrocalcinosis) [ 82 , 83 ]. Weakness, anorexia, loss of skin turgor, weariness, bone aches and dry mucous membranes (due to dehydration), changes in mental status, stomach soreness without rebound, rigidity, or guarding may occur as non-specific symptoms [ 83 ].…”
Section: Toxicokinetics and Case Reports Of Vitamin D Toxicity In Ped...mentioning
confidence: 99%